Makna Filosofis Teks Panyandra pada Upacara Panggih dalam Pernikahan Adat Jawa - Prastawa, Muhammad Rizki Tri; Werdiningsih, Yuli Kurniati; Zaidah, Nuning (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to explore the philosophical meanings embedded in the panyandra text during the panggih ceremony in Javanese traditional weddings. The objective of the research is to understand the reflection of cultural values, the knowledge conveyed by the panyandra text, and the essence experienced by the bride and groom in their marital bond. The research employs a qualitative text analysis method, enabling a deep exploration of the meanings within the panyandra text in the context of the panggih ceremony. The findings reveal that the panyandra text not only conveys cultural values and the essence of marriage but also contains implicit prayers and supplications that reflect the desire for strong life guidance, adequate wisdom, and closeness to God in seeking divine approval. Furthermore, the philosophical meanings found in the panyandra text, particularly in the balangan gantal, midak antiga/wiji dadi, and wijikan sections, emphasize that the creation of a harmonious household and the fulfillment of marital goals can only be achieved through pure love, sincerity, selflessness, and the upholding of tolerance.The theoretical implications of this study underscore the depth of the philosophical meanings in the panyandra text during the panggih ceremony in Javanese traditional weddings, which are relevant to cultural, religious, and social norms. This research is expected to enrich public knowledge of Javanese culture and contribute to cultural revitalization, particularly in the fields of cultural anthropology, Javanese literature, and traditional ceremonies.